More Security Issues are Needed on the European Union Agenda: Beyond an Academic Concept of In/Security in the Era of Global Terrorism - Oldřich Krulík; Buhoslav Pernica; Libor Stejskal; Jakub Kašík (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
Security as an objectively existing quality which can be discussed in innumerable ways, but it may hardly be ignored and its significance (let alone its existence) may hardly be doubted. Security is a fundamental human need which is a subject of our efforts for its satisfaction and its chronic deficiency leads to frustration. Considering the differing views on how the term "security" itself should be defined and what specific aspects or issues it should include (and which ones it should not), there can be no doubt that virtually no area of human activity can manage without holding an opinion on security issues. Security is not a mere construct inferred from academic debates. Nothing can change this despite the fact that this phenomenon has become an overused topic of societal debates, election campaigns and media (virtual) reality. Presence or absence of danger (in/security, un/certainty) can be described in so many forms, that are not easy to be transparently arranged or even mathematized. It is in fact necessary to give up the quest for the objective truth, because of the fact, that the security disciplines are very subjective per se. Security is an omnipresent phenomenon and it is difficult to choose the best concept for a security research for this reason, although many authors are insisting on their concept being the best one. This paper deals with these matters presenting an academic concept of in/security in the context of a revise of the security agenda of the European Union (e.g. with regard to the Directive of the Council on the identification and designation of European Critical Infrastructure and the assessment of the need to improve their protection.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: D74; H41; H87; 330; security; safety; concept; risk; threat; security policy; terrorisms; European Union